Formation of Cross-Cultural Values of Pupils at Schools of AR of Crimea as Scientific-Pedagogigcal Problem - Zaredinova, Elvira; Ziyadinova, Riyana (Pedagogical Discourse, 2012)
This article deals with the scientific and pedagogical bases of the problem of formation of pupils’ cross-cultural values in Crimean schools. On the bases of analysis of psychological and pedagogical literature the key areas of work to form cross-cultural values are identified.